PALLADIUM, PLATINUM AND GOLD MINERAL ASSEMBLAGES IN ORES OF THE NORILSK DEPOSIT - Spiridonov É.M.; Kulagov É.A.; Kulikova I.M. (My University, 2004)
Peculiar mineralization of noble metals, which includes several generations of gold-bearing minerals, is described. These minerals make up metasomatic ingrowths in magmatic galena-magnetite-pentlandite-cubanite-talnakhite ores of the Norilsk deposit. The early assemblage consists of tetraferroplatinum with thin Au-Pt-Pb-atokite lamellae and Au-Pt-Pb-atokite with thin tetraferroplatinum lamellae, products of their collective recrystallization. The late assemblage consists of tetraferroplatinum without exsolution textures, rustenburgite-atokite zoned segregations, zvyagintsevite, stannopalladinite, and Pt-Pd-tetraauricupride that replaced the early Pt and Pd minerals. These forms are overgrown with Pd-tetraauricupride. Küstelite and polarite make up overgrowing and replacement rims on Pd-tetraauricupride, tetraferroplatinum, and zvyagintsevite. The composition of Au-Pt-Pb-atokite varies from [(Pd2.8Pt0.1Au0.1 (Sn0.5Pb0.5)] to [(Pd2.3Pt0.6Cu0.1 (Sn0.9Pb0.1)], that of atokite corresponds to [(Pt1.3-0.3Pd1.6-2.7 Cu0.1-03(Sn1-0.8Pb0-0.2)], rustenburgite [(Pt2.1-1.5Pd0.8-1.4Cu0.13Sn], zvyagintsevite from [Pd3Pb] to [(Pd2.6Pt0.3Au0.1 (Pb0.5Sn0.5)], stannopalladinite [(Pd4.9-4.5Pt0.1-0.55Cu(Sn1.8-1.1Pb0.1 -0.5Sb0.1-0.4)2], and polarite [Pd2PbBi0.9Sb0.1]. The contents of Ni and Cu in tetraferroplatinum [Pt2Fe(Fe, Ni,Cu ] are 2-4 wt %; those of Pd and Pt in tetraauricupride [CuAu] are 4-5 and 3-7 wt %, respectively. The Au content in other forms is as follows, wt %: 1.5-3 in early atokite, up to 1 in late atokite, 1.3-2.7 in zvyagintsevite, 0.1-0.6 in stannopalladinite, and 0.5-1.3 in polarite. The fineness of küstelite is 300-267 ‰. The peculiarities of the minerals described are a high Pb content and low As and Te contents. They formed during the replacement of galena, talnakhite, cubanite, and pentlandite under sharply reducing conditions. Pt, Pd, Au, Ag, Sn, and Bi were transported in the fluid phase, whereas Pb, Cu, and Fe were input from replaced minerals of sulfide ores. Judging from the availability of tetraauricupride, the process of Pd, Pt, Ag, and Au formation proceeded at a temperature below 410°C.